2004
DOI: 10.1038/sj.gene.6364145
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping chromosome 16q12 in a collection of 231 systemic lupus erythematosus sibpair and multiplex families

Abstract: Systemic lupus erythematosus (SLE) is a chronic, autoimmune disorder influenced by multiple genetic and environmental factors. Linkage of SLE to chromosome 16q12-13 (LOD score ¼ 3.85) was first identified in pedigrees collected at the University of Minnesota, and has been replicated in several independent SLE collections. We performed fine mapping using microsatellites to further refine the susceptibility region(s), and the best evidence for linkage was identified at marker D16S3396 (LOD ¼ 2.28, P ¼ 0.0006). E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Systemic lupus erythematosus (SLE) is a prototype autoimmune disease with relatively strong genetic components that genome wide linkage scans performed in the past decade have identified chromosome 16p12.3 to q12.2 to be the second-strongest locus linked to SLE after HLA (6p22.3 to 6p21.1) [1-8]. A positional candidate gene, ITGAM located at 16p11.2, has been recently identified and validated as a lupus susceptibility gene by different groups [9-11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systemic lupus erythematosus (SLE) is a prototype autoimmune disease with relatively strong genetic components that genome wide linkage scans performed in the past decade have identified chromosome 16p12.3 to q12.2 to be the second-strongest locus linked to SLE after HLA (6p22.3 to 6p21.1) [1-8]. A positional candidate gene, ITGAM located at 16p11.2, has been recently identified and validated as a lupus susceptibility gene by different groups [9-11].…”
Section: Introductionmentioning
confidence: 99%
“…A positional candidate gene, ITGAM located at 16p11.2, has been recently identified and validated as a lupus susceptibility gene by different groups [9-11]. However, fine mapping experiments of the chromosome 16p locus have shown multiple association signals clustering in several regions [8,12], suggesting more than one gene may be involved in the increased risk of SLE.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11] Linkage studies in human SLE pedigrees have identified multiple regions that meet genomewide criteria for significant or suggestive linkage, 12 which is consistent with the hypothesis that SLE is a complex polygenic disease. [13][14][15][16][17][18][19][20][21][22][23][24][25][26] Our group was one of the first to provide evidence for linkage on chromosome 20 (D20S186, LOD p ) in an initial study of 105 SLE sib pair pedigrees. 15…”
mentioning
confidence: 99%
“…At least four independent study groups reported the evidence of SLE linkage in this region. Recently, two independent replication studies confirmed this linkage (Nath et al 2004a, b;Gillett et al 2005). Interestingly, a Chinese group using a familybased association test, found an association between OAZ gene at 16q12 and SLE in Chinese population (Feng et al 2003(Feng et al , 2004.…”
Section: Discussionmentioning
confidence: 74%